A Comprehensive Evaluation of the Supreme Court's Forest Grove Decision?. (June 2013) - Zirkel, Perry A.
The article by Dixon, Eusebio, Turton, Wright, and Hale is entitled " Forest Grove School District v. T.A . Supreme Court Case: Implications for School Psychology Practice." Its implications are that a "comprehensive evaluation" under the Individuals with Disabilities Education Act (IDEA) requires assessment of the child's cognitive neuropsychological as well as academic and psychosocial functioning and, thus, must include cognitive assessment in the identification of specific learning disabilities. However, neither the Supreme Court's Forest Grove decision nor the other legal authority that Dixon et al. cited provide such a requirement. Instead, the applicable federal regulations and case law generally are far less detailed and definitive in prescribing appropriate evaluations under the IDEA. This discrepancy illustrates the need of the special education and school psychology literature to improve the legal information and understanding of practitioners by more careful differentiation of analysis and advocacy that does not confuse legal requirements with professional norms.